2021
DOI: 10.18196/jai.v22i2.11337
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ownership Structures on Audit Fees of Listed Firms in Ghana

Abstract: Research aims: The study examined the effect of ownership structures on audit fees of listed firms in Ghana. The study used four indicators to measure ownership structure: managerial ownership, foreign ownership, government ownership, and substantial (block) ownership.Design/Methodology/Approach: The study sampled 21 listed non-financial firms over ten years, covering the period 2010 to 2019. The study also relied on secondary data extracted from the financial statement of these listed firms. Data were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 32 publications
6
12
0
Order By: Relevance
“…The revelation from the study is that an inverse relationship exists between CEO succession with gender change and audit fee that is paid but the negative effect was found to be less in state-owned firms as compared to firms not owned by the state. In addition, Musah et al (2022) report no significant impact of female CEO on audit fee. Conversely, studying the impact of demographic characteristics of CEOs and directors on audit fees and audit delay, Harjoto et al (2015) found that firms with female and ethnic minority CEOs pay significantly higher audit fees than those with male Caucasian CEOs.…”
Section: Empirical Literature Review and Hypothesis Developmentmentioning
confidence: 91%
See 3 more Smart Citations
“…The revelation from the study is that an inverse relationship exists between CEO succession with gender change and audit fee that is paid but the negative effect was found to be less in state-owned firms as compared to firms not owned by the state. In addition, Musah et al (2022) report no significant impact of female CEO on audit fee. Conversely, studying the impact of demographic characteristics of CEOs and directors on audit fees and audit delay, Harjoto et al (2015) found that firms with female and ethnic minority CEOs pay significantly higher audit fees than those with male Caucasian CEOs.…”
Section: Empirical Literature Review and Hypothesis Developmentmentioning
confidence: 91%
“…To address the specific objective of the study, the specific regression model for the study was developed following the works of Miglani and Ahmed (2019), Alkebsee et al (2020), Gull et al (2021) and Musah et al (2022), but with modifications and inclusion of new gender variables. However, for purposes of estimation, ordinary least square (OLS) estimation and generalized least square (fixed-effect estimation technique) were used.…”
Section: Research Methodology and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it can encourage managers not to do detrimental things to investors or opportunistic behavior to maximize the manager's work in improving financial performance. According to (Musah et al, 2021), control in companies with dispersed ownership significantly lies with management. Managers can use this opportunity to fulfill their interests at the expense of shareholders.…”
Section: Government Ownership and Firm Performancementioning
confidence: 99%